Analysis of fault characteristics and oil and gas enrichment differences in the No. 2 structural belt, Nanpu Sag, Bohai Bay Basin, East China - Zou, Juan; Liu, Guoyong; Ma, Qian; Yu, Fusheng; Meng, Lingjian; Tian, Bo (Frontiers in Earth Science, 2023)
There are great differences in oil and gas enrichment at different locations in petroliferous basins, and faults are an important factor affecting the differential enrichment of oil and gas. In this paper, taking the No. 2 structure in the Nanpu Sag, Bohai Bay Basin, East China, as an example, based on the analysis of fault geometry and kinematics characteristics, the determination of oil source faults, the analysis of fault trap origin and effectiveness, and the analysis of fault caprock combinations are carried out to study the differences and mechanisms of oil and gas enrichment east and west of the Nanpu No. 2 structure. The results show that the fault-source contact relationship affects the direction of oil and gas migration. The No. 2 structure in the Nanpu Sag has a dual-source hydrocarbon supply. The western structure supplies hydrocarbons from the north and east, with oil and gas migrating along the direction parallel and perpendicular to the fault strike. The east structure supplies hydrocarbons from the south and north, with oil and gas migrating along the direction perpendicular to the fault strike. The effectiveness of fault traps affects the scale of oil and gas accumulation. Most of the traps of the Nanpu No. 2 structure formed before hydrocarbon expulsion, which are all effective traps and are conducive to oil and gas accumulation. The relationship between fault and caprock determines the vertical accumulation layers of oil and gas: The faulted thickness of the east structure is large, the fault is vertically closed, and oil and gas are enriched mainly in the deep layer. The faulted thickness of the west structure is small, and oil and gas are enriched in both deep and shallow layers.